1992
DOI: 10.1139/m92-052
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of thermotolerant campylobacters in fresh vegetables sold at farmers' outdoor markets and supermarkets

Abstract: A total of 1564 fresh samples of 10 vegetable types from two different retail levels (533 samples from farmers' outdoor markets and 1031 samples from supermarkets) were surveyed for the occurrence of thermotolerant campylobacters. In samples from the outdoor markets, campylobacters were detected on six types of vegetables; the detection rates were spinach, 3.3; lettuce, 3.1; radish, 2.7; green onions, 2.5; parsley, 2.4; and potatoes, 1.6%. Campylobacter jejuni was the predominant species (88%), with the remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
53
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 32 publications
1
53
1
Order By: Relevance
“…Kumar et al [20] reported that out of 56 vegetables samples examined, two (3.57%) revealed the presence of Campylobacter spp. Park and Sanders [57] reported that 1 of 40 leafy vegetables samples, 2 of 67 lettuce samples, 1 of 63 pepper and 2 of 60 spinach samples were positive for Campylobacter spp., respectively. Verhoeff -Bakkenes et al [21] noted that 10 of 4691 (0.21%) vegetables samples, 2 of 790 (0.25%) fruits samples were positive for Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al [20] reported that out of 56 vegetables samples examined, two (3.57%) revealed the presence of Campylobacter spp. Park and Sanders [57] reported that 1 of 40 leafy vegetables samples, 2 of 67 lettuce samples, 1 of 63 pepper and 2 of 60 spinach samples were positive for Campylobacter spp., respectively. Verhoeff -Bakkenes et al [21] noted that 10 of 4691 (0.21%) vegetables samples, 2 of 790 (0.25%) fruits samples were positive for Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…C. jejuni has been isolated previously from these plant species at outdoor markets (28,34). Plant surfaces are hostile environments for most microorganisms because of prevailing rapid and repeated fluctuations in temperature, water availability, and radiation (22).…”
Section: Discussionmentioning
confidence: 99%
“…This scenario is highly probable and would explain the unexpectedly high number of produce-related outbreaks compared to those related to other food sources. Nevertheless, it is noteworthy that several studies have reported the presence of Campylobacter species on produce sampled at the marketplace, including spinach, lettuce, radish, green onion, parsley, and potatoes (34), ready-to-eat grated carrots and cabbage (17), modified-atmosphere packaged mixed salad vegetables (35), mushrooms (14), and spinach and fenugreek (28).…”
mentioning
confidence: 99%
“…Much lower levels; 3.1%, 3.57%, and 7.5% have also been reported in Canada, India and Brazil, respectively (Park and Sanders, 1992;Kumar et al, 2001;Carvalho et al, 2013). Contamination levels of 18.8% and 35.2% have also been reported by Chai et al, (2009) and Khalid et al, (2014) in farm vegetables.…”
Section: Resultsmentioning
confidence: 88%
“…In our market vegetables, 61.5% were C. jejuni and 23.0% C. coli and 50% and 21.4% were C. jejuni and C. coli in the farm vegetables. In Canada, Park and Sanders (1992) reported 88% of C. jejuni and 4% C. coli in vegetables purchased from outdoor markets and supermarkets while in Malaysia, Chai et al, (2007) reported 40.7% C. jejuni and 35.2% C. coli from supermarkets. The high isolation rate of C. jejuni as opposed to C. coli supports the theory that C. jejuni is more resilient to environmental stresses (Gonzalez and Hänninen, 2012;Bronowski et al, 2014); as Chai et al, (2009) also failed to isolate C. coli from soil and manure in Malaysia.…”
Section: Resultsmentioning
confidence: 99%